Doxorubicin increases permeability of murine small intestinal epithelium and cultured T84 monolayers - Cray, Paul (Sci Rep, 2020)
Enteric bacteria and/or their products are necessary for doxorubicin (DXR)-induced small intestine mucosal damage. While DXR does not induce gross loss of epithelium, others have shown elevated serum endotoxin after DXR administration. However, the mechanism of movement is unknown. We hypothesized that DXR treatment resulted in increased paracellular translocation of bacteria or bacterial products through the small intestinal epithelium. We measured permeability after DXR administration using transepithelial resistance and macromolecular flux and assessed tight junctional gene expression and protein localization both in vitro using T84 cells and ex vivo using murine jejunum. DXR treatment increased flux of 4 kDa dextrans in mouse jejenum, but increased flux of 4, 10 and 20 kDa dextrans in T84 cells. Following DXR, we observed increased permeability, both in vitro and ex vivo, independent of bacteria. DXR induced increased expression of Cldn2 and Cldn4 in murine small intestine but increased only CLDN2 expression in T84 cells. DXR treatment induced disorganization of tight junctional proteins. We conclude that DXR increases paracellular transit of small macromolecules, including bacterial products, through the epithelium, by altering expression of tight junctional components and dynamic loosening of cellular tight junctions.